Pre-treatment effect on the transport properties of sulfonated poly(ether ether ketone) membranes for DMFC applications - Silva, V (2006)
Liquid feed direct methanol fuel cells (DMFCs) employing proton-exchange membranes (PEMs) are promising candidates for portable power applications [1]. However, the use of perfluorinated membranes as polymer electrolyte leads to a significant decrease in the fuel cell Faraday efficiency due to methanol crossover [1]. Nonfluorinated membranes based on sulfonated poly(ether ether ketone) (sPEEK) have been presented as promising materials due to their high proton conductivity [2]. Also, in order to improve the membrane properties for DMFC applications, the single-phase sPEEK polymer was modified by the incorporation of zirconium oxide (ZrO2), which decreases the methanol permeation [3]. Furthermore, the membrane properties are also influenced by proper sample pre-treatment. The present study aims to characterize sPEEK membranes and to perform a critical study regarding the pre-treatment effects on the membrane properties. Nafion® 1135 (from Aldrich) was used as reference material.